Study on the influence of family capital on Chinese adolescents’ subjective well-being - Wu, Xiling; Liu, Zhiyan; Lin, Youchang (Frontiers in Psychology, 2022)
Subjective well-being (SWB) is an important part of positive psychology research.Compared with other countries and regions, Chinese adolescents’ well-being level is relatively lower. Under the guidance of ecological systems theory, this study is based on the survey data of PISA 2018, with 10,805 middle school students from four provinces and cities in China (Beijing, Shanghai, Jiangsu, Zhejiang) as the research samples, and examines the theoretical model of the influence of family capital on adolescents’ subjective well-being by means of structural equation modelling, in which the effects of family capital, school climate and academic achievement on adolescents’ subjective well-being are discussed. The empirical results show that family capital directly and indirectly negatively influences adolescents’ subjective well-being through academic achievements, and indirectly positively influences adolescents’ subjective well-being through school climate. School climate directly positively affects adolescents’ subjective well-being, and indirectly negatively influences adolescents’ subjective well-being through their academic achievement. Academic achievement negatively affects adolescents’ subjective well-being. The research results strongly support the correctness of the theoretical framework, indicating the complexity of the formation of adolescents’ subjective well-being.